Analisis Hubungan Ketinggian Planetary Boundary Layer (PBL) dengan Surface Flux di Makassar dan Sekitarnya - Juliana Tri Lestari; Eko Hadi Sujiono; Muhammad Arsyad (Jurnal Fisika Unand, 2024)
Planetary Boundary Layer (PBL) is influenced by the processes of transfer of momentum, energy, and materials between tPBL and surface layer. Surface fluxes variables consist of Sensible heat flux (SHF) and Latent heat flux (LHF), these variables are also used to measure transport level in this process. Madden Julian Oscillation also contribute in the PBL condition. Therefore, this study was aimed to describe the SHF/LHF and PBL profiles during strong and weak Madden-Julian Oscillation (MJO) periods around Makassar area and its relationship. PBL height was obtained by using the Bulk Richardson Number (Rib) method and bulk aerodynamic for SHF/LHF. Then correlation analysis was done between these two variables. SHF in both strong and weak MJO at 12.00 UTC have greater value than 00.00 UTC, while LHF showed the opposite. PBL height tends to be higher at 00.00 UTC than 12.00 UTC, with the average values were between549,9 to 690,5 m. Annual mean of PBL height ranged between 470 to 1100 m. Maximum average PBL occurred during the transition season I (MAM) at 00.00 UTC, while the minimum happened during transition season 2 (SON) at 12.00 UTC. However, the PBL height profile had shown weak correlation to SHF/LHF value during both MJO strong and weak in Makassar Area.